2001
DOI: 10.1254/jjp.85.139
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Prostaglandin E2 in Clearance of Aggregated Protein via Protein Kinase A in Glomeruli

Abstract: ABSTRACT-Recently we immunohistochemically demonstrated that prostaglandin E2 (PGE2) promoted the clearance of aggregated bovine serum albumin (a-BSA) deposited in glomeruli. Herein, we investigated the role of PGE2 and its signal transduction in the disposal of macromolecules in glomeruli. EP2 and EP4 receptor mRNA was detected in glomeruli by RT-PCR analysis. A-BSA was injected twice into mice. Glomeruli were then isolated and incubated. A-BSA gradually disappeared from isolated glomeruli. PGE 2 increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Prostaglandin e 2 stimulates production of cyclic amP via eP2 and eP4 prostaglandin e receptors in isolated glomeruli [6,7,14]. we have demonstrated that isolated glomeruli generate prostaglandin e 2 and that a-Bsa increases the expression of cyclooxygenase-2 mrNa and cyclooxygenase-2 activity followed by the expression of prostaglandin e 2 [5].…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Prostaglandin e 2 stimulates production of cyclic amP via eP2 and eP4 prostaglandin e receptors in isolated glomeruli [6,7,14]. we have demonstrated that isolated glomeruli generate prostaglandin e 2 and that a-Bsa increases the expression of cyclooxygenase-2 mrNa and cyclooxygenase-2 activity followed by the expression of prostaglandin e 2 [5].…”
Section: Discussionmentioning
confidence: 69%
“…we expected the inhibitor of PKa, not PKC, to suppress the phosphorylation, having demonstrated that a-Bsa activated the cyclic amP-PKa system in isolated glomeruli using pharmacological manipulations [6]. other investigators have clarified the ability of isolated glomeruli and mesangial cells to accumulate camP in response to various agonists [10,11].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations